2006
DOI: 10.1085/jgp.200509423
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sialylation Modulates Voltage-gated Na+ Channel Gating throughout the Developing Myocardium

Abstract: Voltage-gated sodium channel function from neonatal and adult rat cardiomyocytes was measured and compared. Channels from neonatal ventricles required an ∼10 mV greater depolarization for voltage-dependent gating events than did channels from neonatal atria and adult atria and ventricles. We questioned whether such gating shifts were due to developmental and/or chamber-dependent changes in channel-associated functional sialic acids. Thus, all gating characteristics for channels from neonatal atria and adult at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
67
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 47 publications
9
67
1
Order By: Relevance
“…4, left panels). These data are consistent with our previous report indicating Na v sialylation impacts channel gating in the neonatal atrium but not in the neonatal ventricle (15). These data also correlate with the AP data.…”
Section: Regulated and Aberrant Expression Of A Single Glycogene Modusupporting
confidence: 93%
See 4 more Smart Citations
“…4, left panels). These data are consistent with our previous report indicating Na v sialylation impacts channel gating in the neonatal atrium but not in the neonatal ventricle (15). These data also correlate with the AP data.…”
Section: Regulated and Aberrant Expression Of A Single Glycogene Modusupporting
confidence: 93%
“…To determine whether the remodeled glycome modulates cardiac function, we observed the impact of the regulated and aberrant expression of a single glycogene on cardiomyocyte electrical activity. We studied the effect of the polysialyltransferase, ST8sia2 (responsible for addition of sialic acid polymers to N-and O-glycans), on cardiac function for several reasons that include: (i) Cardiac dysfunctions including arrhythmias and cardiomyopathy that are likely caused by changes in ion channel activity are prevalent in diseases of aberrant sialylation such as Chagas disease and some CDGs (16 -19); (ii) all our previous data indicated that changes in ion channel sialylation contribute significantly to the modulation of ion channel function (11)(12)(13)15); and (iii) cardiac ST8sia2 expression is regulated. ST8sia2 is expressed at much higher levels in the neonatal atrium than in the neonatal ventricle as determined through microarray ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations